CXCR4 expression of multiple myeloma as a dynamic process: influence of therapeutic agents. Issue 10 (24th August 2022) - Bögelein, Anna; Stolzenburg, Antje; Eiring, Patrick; Lückerath, Katharina; Munawar, Umair; Werner, Rudolf; Schirbel, Andreas; Samnick, Samuel; Kortüm, Klaus Martin; Sauer, Markus; Lapa, Constantin; Buck, Andreas K.
Abstract: Chemokine receptors represent novel targets for treatment of multiple myeloma (MM). However, CXCR4 expression appears to be highly dynamic. This in vitro study investigated the impact of commonly used anti-myeloma agents on CXCR4 expression. Established human myeloma cell lines as well as patient-derived CD138 + plasma cells were exposed to antineoplastic drugs. Cells were analyzed for CXCR4 expression by flow cytometry and direct stochastic optical reconstruction microscopy ( d STORM). In addition, cellular uptake of 68 Ga-Pentixafor, a PET radiotracer for noninvasive assessment of CXCR4 expression in vivo, was assessed. CXCR4 expression was highly variable and turned out to be substance, dose and time dependent. Treatment with bortezomib was associated with reduced expression, while dexamethasone and doxorubicin significantly increased expression of CXCR4. Combination of these compounds further increased CXCR4 expression. In conclusion, drugs or combination of drugs can induce CXCR4 expression in myeloma cells. Hence, pretreatment may impact on response to CXCR4-based therapies.